PENGARUH LOKASI DAN HARGA TERHADAP KEPUASAN WISATAWAN DI TAMAN SARI GUA SUNYARAGI CIREBON - Nurul Eka Faradilla; Setyo Widiarto; Muhamad Arsyad (LPPM and Travel Operation Department Universitas Asa Indonesia, 2021)
Tourist satisfaction is one indicator to increase the competitiveness of a tourist attraction. Location and price are two factors that are believed to contribute positively to tourist satisfaction. This study aims to analyze the effect of location and price variables on tourist satisfaction at Taman Sari Cave Sunyaragi Cirebon Tourist Attraction. A total of 100 tourists were involved as research respondents. The analysis technique uses multiple linear regression. The research instrument uses a questionnaire that has been tested for validity and reliability. Classical assumption tests were carried out including tests of normality, heteroscedasticity, multicollinearity and linearity. The results showed that the location and price variables partially and simultaneously affect tourist satisfaction, and contributed 68.1%, while the remaining 31.9% is influenced by other variables not discussed in this study such as perceived value, tangibles, reliability, assurance, empathy, and responsibility.